2018
DOI: 10.24200/sci.2018.5101.1096
|View full text |Cite
|
Sign up to set email alerts
|

How does long trip affect on driving performance, eye blinks and awareness of sleepiness among commercial drivers? A naturalistic driving test study

Abstract: Abstract. A total of 120 commercial drivers from four age groups participated in the expressway driving test in Shandong, China, to perform continuous driving tasks of 2, 3, and 4 h and collect the data on the driver's blinking, driving performance, and self-reported level of sleepiness. A two-way repeated measures ANOVA was used to evaluate the e ects of driving duration on the variation of the eye-blink behavior, driving performance, and subjective feeling of sleepiness across the di erent age groups over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In parallel, a multi-sensor system consisting of infrared thermometer and reflective optical sensor for measuring pulse oximetry and skin temperature implemented in the S-Class Mercedes was published by Heuer et al [ 98 ]. In parallel, D’Angelo et al [ 8 , 9 ] demonstrated a multi-sensor system integrated into the steering wheel of the BMW 730d test vehicle, which enabled pulse oximetry and conductive ECG scanning. They applied a similar design to the one proposed by Jeong et al [ 94 ], which integrated the electrodes into the steering wheel, the gear shift and the left armrest.…”
Section: Overview Of Already Existing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, a multi-sensor system consisting of infrared thermometer and reflective optical sensor for measuring pulse oximetry and skin temperature implemented in the S-Class Mercedes was published by Heuer et al [ 98 ]. In parallel, D’Angelo et al [ 8 , 9 ] demonstrated a multi-sensor system integrated into the steering wheel of the BMW 730d test vehicle, which enabled pulse oximetry and conductive ECG scanning. They applied a similar design to the one proposed by Jeong et al [ 94 ], which integrated the electrodes into the steering wheel, the gear shift and the left armrest.…”
Section: Overview Of Already Existing Methodsmentioning
confidence: 99%
“…Even a short diversion caused by a reflection in the rear-view mirror can affect the whole journey and lead to major accidents [ 5 , 6 ]. Long journeys also lead to fatigue; therefore, it can be very challenging to keep constant attention on the road [ 7 , 8 ]. As living standards increase, so does the number of vehicles and thus the density of traffic and the number of traffic accidents [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study done in China on commercial drivers found that as the age of the drivers increased, there was a higher likelihood they would get sleepy in long-distance driving. Similarly, as the professional drivers' age increased, cognitive speed and reaction time were impacted (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In China, there were 244 937 road crashes in 2018, resulting in 63 194 fatalities and 258 532 injuries. Fifteen percent of these crashes were reported to be directly or indirectly associated with driver drowsiness (Wang, Ma, & Wei, 2019a). In Europe, the average prevalence of falling asleep at the wheel in 2014 and 2015 was 17%.…”
Section: Introductionmentioning
confidence: 99%